Intradural extramedullary cavernous malformation with extensive superficial siderosis of the neuraxis: Case report and review of literature - Golnari, Pedram (Surg Neurol Int, 2017)
BACKGROUND: Spinal cavernous malformations usually affect the vertebral bodies and are seldom intradural. Here, we report a rare spinal intradural-extramedullary cavernous malformation associated with extensive superficial siderosis along the neuraxis in a patient with radicular complaints. CASE DESCRIPTION: A 60-year-old male presented with subacute headaches, intermittent fever, and acute back and radicular leg pain for 1–2 weeks. Magnetic resonance imaging revealed an intradural-extramedullary lesion just below the conus medullaris (at the L2 level). There was associated subarachnoid hemorrhage in the lumbar cistern and superficial siderosis along the entire spinal neuraxis. Following surgical resection, the patient's symptoms resolved. Histopathology of the lesion was of a cavernous malformation. CONCLUSIONS: There are only 56 cases of spinal intradural-extramedullary cavernous malformations published in the literature; however, only 3 described superficial neuraxis siderosis as noted in this case. In the present case, slowly recurring hemorrhages of the lesion located at the conus likely contributed to the complete neuraxis superficial siderosis. Timely evaluation and treatment of these lesions is warranted to avoid further compressive and/or hemorrhagic complications.